Radiographic assessment of the influence of metopism in frontal sinus morphology – a systematic review (Research, Society and Development, 2020)
Objective: This systematic literature reviews aimed to revisit radiographic observational studies the find out the potential influence of metopism in frontal sinus (FS) development. Methodology: Medline, Scopus, SciELO, LILACS and Web of Science databases were searched. Only cross-sectional and case-control original studies were eligible. Two reviewers independently participated in each phase of this review. General, methodological and outcome-related information of each study were extracted. Risk of bias was assessed with the Joanna Briggs Institute (JBI) Critical Appraisal tool for observational studies. Based on the limitations of each study, recommendations were made following EQUATOR/STROBE guidelines. Results: Depicted in an adapted PRISMA flowchart, three-hundred and sixty-five studies were identified and seven (published between 1959-2019) remained for qualitative analysis. Without considering studies with overlapping samples, five-hundred and nine skulls with metopism were detected. FS aplasia reached a prevalence of nearly 13%. Four studies (three with overlapping samples) observed a tendency of FS underdevelopment in skulls with metopism, while three studies suggested the opposite. Higher risk of bias was found in the latter. Conclusion: The available and most recent scientific literature points toward an eventual influence of metopism in FS underdevelopment. Due to the study of overlapping samples and the lack of standardized reporting protocols of methods and outcomes, however, the evidence extracted in the present systematic literature review does not confirm the association of FS underdevelopment and metopism.